Changes in the spatial structure of the automotive industry in Brazil at the turn of the 20th and 21st century - Wójtowicz, Mirosław (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
In recent decades, the automotive industry in Brazil has undergone a profound transformation connected with the modernization of production, increase in the efficiency and quality of produced vehicles. These processes took place in a situation of progressive liberalization of the economy, regional integration within Mercosur and globalization. The high rate of economic growth and stability in the country contributed to the rapid growth in demand for new vehicles. Local factories struggled to keep up with the rising demand and have noted the new production records each year. The rapid growth of sales on the domestic market and in the neighboring countries has prompted international companies to further investments to expand production capacity in Brazilian car factories. New foreign investments arriving in Brazil radically changed the spatial structure of the automotive industry. In the early 1990s, 75% of the cars came from the state of São Paulo, whereas in 2012, its share fell to 41.5%. The new production centers appeared in the states of Parana, Bahia, Rio Grande do Sul, Rio de Janeiro, and further investments are in progress. The purpose of this article is to determine the changes in the spatial structure of the automobile industry in Brazil in the period 1996-2011. Furthermore, the author attempts to determine whether the investments made in the last two decades led to the emergence of new spatial agglomerations of the automotive industry.